Winter dynamics of functional diversity and redundancy of riffle and pool macroinvertebrates after defoliation in a temperate forest stream - Wang, Lu; Xia, Lixian; Li, Jiaxu; Wan, Linglin; Yang, Haijun (Frontiers in Microbiology, 2023)
Headwater streams are highly heterogenous and characterized by a sequence of riffles and pools, which are identified as distinct habitats. That higher species richness and density in riffles than in pools is considered a general pattern for macroinvertebrates. As temperate winters can last long up to half a year, however, macroinvertebrate communities of riffles and pools may assemble differently under ices or snows. Particularly, defoliation concentrating in autumn can largely change habitats in both riffles and pools by litter patching. According to the absence or presence of litter patches, there exist four types of subhabitats, i.e., riffle stones, riffle litters, and pool sediments, pool litters, which are selectively colonized by macroinvertebrates. To study the spatial pattern and temporal dynamics of colonization, macroinvertebrates were surveyed in a warmer temperate forest headwater stream in Northeast China during four periods: autumn, pre-freezing, freezing and thawing periods. Our study focused on functional trait composition, functional diversity and functional redundancy of macroinvertebrate communities. The colonization of macroinvertebrates was found to be significantly different in these subhabitats. Riffle stones supported higher taxonomic and functional diversities than pool sediments; litter patches supported higher total macroinvertebrate abundance and higher functional redundancy than riffle stones or pool sediments. The functional trait composition changed significantly with seasonal freeze-thaw in both riffle stones and pool sediments, but not in litter patches. Macroinvertebrate community in litter patches showed seasonal stability in taxonomic and functional diversities and functional redundancy. Thus, this study strongly highlights that litter patches play an important role structuring macroinvertebrate community over winter, supporting high abundance and maintaining functional stability.